2013
DOI: 10.1016/j.paid.2013.07.471
|View full text |Cite
|
Sign up to set email alerts
|

Believe it or not: Exploring the relationship between dogmatism and openness within non-religious samples

Abstract: Personality and dogmatic thinking within religious individuals have been examined by previous research, but neglected for non-religious individuals. In this experiment, we distinguish between two types of non-religious groups; those who ascribe themselves to an identity (atheists) and those who do not (no beliefs in particular). A total of 103 nonreligious individuals (36% atheists and 64% with no particular beliefs) completed an online questionnaire measuring dogmatism and openness traits, with an additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Scholars have established that, for as long as there have been records of religion there have also been dissenters who reject the gods (Whitmarsh 2016), sometimes vocally (Jacoby 2005) but other times in secret in order to avoid persecution (Hecht 2004). Such individuals will have a proclivity to reject supernatural belief, will be dispositionally inclined toward openness (Williams & Roberts 2016; though see Gurney et al 2013;Saroglou 2002), and will be able and willing to suffer the consequences of their decisions (Rogers 2006;Edgell, Frost & Stewart 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Scholars have established that, for as long as there have been records of religion there have also been dissenters who reject the gods (Whitmarsh 2016), sometimes vocally (Jacoby 2005) but other times in secret in order to avoid persecution (Hecht 2004). Such individuals will have a proclivity to reject supernatural belief, will be dispositionally inclined toward openness (Williams & Roberts 2016; though see Gurney et al 2013;Saroglou 2002), and will be able and willing to suffer the consequences of their decisions (Rogers 2006;Edgell, Frost & Stewart 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition, those people with a tendency toward rigid, dogmatic attitudes held more negative attitudes towards service dogs. Studies have shown attitude is a strong predictor of behaviour (Ajzen, 1991;Koger & Winter, 2010;Mullan et al, 2015); moreover, people with dogmatic styles of cognition are more resistant to noticing and applying new information (Altemeyer, 2002;Gurney, Mckeown, Churchyard, & Howlett, 2013;Ottati et al, 2015).…”
Section: International Journal Of Orientation and Mobilitymentioning
confidence: 99%
“…These surveys are often used to study the relationship between dogmatism and other psychological phenomena. For example, dogmatic people tend to show an increased tendency for confrontation (El-Nawawy and Powers, 2010) or moral conviction and religiosity (Swink, 2011), and less likelihood of cognitive flexibility (Martin et al, 2011), even among stereotypically non-dogmatic groups like atheists (Gurney et al, 2013). From a behavioral standpoint, dogmatic people solve problems differently, spending less time framing a problem and expressing more certainty in their solution (Lohman, 2010).…”
Section: Related Workmentioning
confidence: 99%